Field evaluation of copper and zinc-coated urea on yield and nitrogen uptake of rice - Mohamed Sazali, Nur Faizatulakma (2017)
The current self-sufficiency level for rice in Malaysia is about 71.4% and the average yield of rice in Malaysia is 3.77 t/ha. Zinc and copper are essential micronutrients for the growth of rice due to their role in plant metabolism and physiological processes and deficiency can greatly reduce rice yield. Urea [(CO(NH2)2] is the most common granular N fertilizer in rice production worldwide but the efficiency of N from added urea in most paddy fields is usually low. Coating the urea granules with polymer or other binding materials seems effective in reducing urea volatilization and leaching. In order to reduce N loss and improve micronutrient status of paddy soils, addition of Zn and Cu-based fertilizers during rice cultivation is essential.The field trial were conducted for 2 seasons consecutively in KADA site in Melur, Kelantan. Rice cultivar, MR219 was used in the experiment for both seasons. While the third season was conducted in MADA site in Tunjang, Kedah using rice cultivar of MR220. The field experiment was designed as a randomized complete block. The treatments consisted of a control and six different types of copper and zinc coated fertilizer combinations namely: 1) urea (control), 2) copper coated urea, 3) copper + urea, 4) zinc coated urea, 5) zinc + urea, 6) copper and zinc coated urea, 7) copper + zinc + urea. Nitrogen was applied as urea (120 kg/ha), while P and K were applied as TSP and MOP with 50 kg of P₂O₅ and K₂O. The paddy was harvested to measure grain yield and the yield components (panicle length, 1000- grain weight, filled and unfilled grain). The plant tissue was analysed for Total N and Cu and Zn using the Kjedahl method and dry ashing method respectively. The soil samples from post-harvested were collected and were analysed for Total N using Kjedahl method, while the concentration of Cu and Zn was determined using dilute double acid method. The data collected were analysed using ANOVA (SAS 9.3), and LSD (P<0.05) was used to test the difference among treatments. The result from all three field experiments showed that application of urea coated fertilizer improved plant growth parameter and nutrient uptake (N, Cu and Zn) in grain over other treatment combinations. However, the addition of Cu and Zn without coated showed no positive effect to the plant growth and yield. Increased in N uptake in plant is due to reduction of N loss by urea inhibitor (Cu and Zn). Nevertheless, coating Cu and Zn to urea managed to avoid them from leaching. Application of Cu and Zn coated urea in season one produced the highest rice yield whereas for seasons two and three, the maximum rice yield was obtained from treatment Zn coated urea. There was large difference of yield between the three season due to two reasons. The first one was due to the different types of soil and the second, was due to the effect of drought. In MADA the soil is made of marine alluvium parent material whereas in KADA the soil is made up from riverine alluvium parent material. In lowland paddy field, water is essential element to maintain good growth. But due to drought, yield in season one is very much reduced compared to seson two.